RESPONSIVITAS PETANI TERHADAP AUDIT DI LEMBAGA KEUANGAN SYARIAH AUDITORS OF FARMERS'S RESPONSIVITY IN THE SHARIA FINANCIAL INSTITUTIONS - Fita Setiati (Politeknik Pertanian Negeri Samarinda, 2019)
The purpose of this study was to determine the perception of farmers on the audit of Islamic financial institutions (LKS) in handling the financing of the needs of farmers in Sukopuro village, Jabung sub-district, Malang regency. This research use desciptive qualitative approach. The population used in this study were the Sukopuro villagers who were members of the Joint Business Group (KUBE). Determination of the sample is done by purposive sampling with the criteria for the community that conducts business and utilizes funds from Islamic financial institutions in the area. The data collection techniques used are observation methods, interviews, documentation and focus discussion groups (FGD). Data analysis in the research in this study by recording data from the results of interviews, observation, documentation and FGD then organized to be sorted out to answer the problem formulation. This analysis is continued by finding and finding meaning related to the formulation of the problem